Peran Green Trust Memediasi Pengaruh Green Brand Image Terhadap Green Brand Equity Pada Produk Hijau - Siwandana, I Komang Lowis; Wardana, I Made (E-Jurnal Manajemen; Vol 6 No 4 (2017), 2017)
Green marketing as one of the marketing strategies that can be applied by marketers to retain customers without a negative impact on the environment. To create an eco-friendly brand can use green trust as one of the variables that are assumed to strengthen the influence of green brand image of green brand equity through the implementation of green marketing. The purpose of this study to prove the determinants that can reinforce brand value of green products Bali Tangi. This study focused on the city of Denpasar by taking the 100 respondents as sample through random sampling method with multiple criteria. This study used a technique confirmatory factor analysis and path analysis. The results of this study prove that green trusts have a role in bridging effect occurs on the variable green brand image of green brand equity. In the future, this research can be used as a reference for companies in implementing policies related to strategies to increase the brand value of green products in a positive direction
Keywords: green marketing, green brand image, green trust, green brand equity